Naloxone Use by Emergency Medical Services During the COVID-19 Pandemic: A National Survey. Issue 6 (December 2020) - Cone, David C.; Bogucki, Sandy; Burns, Kevin; D'Onofrio, Gail; Hawk, Kathryn; Joseph, Daniel; Fiellin, David A.
Abstract : Objectives: The COVID-19 epidemic in the United States has hit in the midst of the opioid overdose crisis. Emergency medical services (EMS) clinicians may limit their use of intranasal naloxone due to concerns of novel coronavirus infection. We sought to determine changes in overdose events and naloxone administration practices by EMS clinicians. Methods: Between April 29, 2020 and May 15, 2020, we surveyed directors of EMS fellowship programs across the US about how overdose events and naloxone administration practices had changed in their catchment areas since March 2020. Results: Based on 60 respondents across all regions of the country, one fifth of surveyed communities have experienced an increase in opioid overdoses and events during which naloxone was administered, and 40% have experienced a decrease. The findings varied by region of the country. Eighteen percent of respondents have discouraged or prohibited the use of intranasal naloxone with 10% encouraging the use of intramuscular naloxone. Conclusions: These findings may provide insight into changes in opioid overdose mortality during this time and assist in future disaster planning.